The Firm [Firma anglicky] - Grisham, John, 1955- (London : Arrow Books, 1993)
The Firm is a 1991 legal thriller by American writer John Grisham. It was his second book and the first that gained wide popularity. In 1993, after selling 1.5 million copies, it was adapted into a film of the same name starring Tom Cruise, Gene Hackman and Jeanne Tripplehorn. Grisham's first novel, A Time to Kill, came into prominence afterwards due to this novel's success.
Keywords: autorské romány; americká literatúra; cudzojazyčná literatúra